Antimalarials – old drugs are new again - Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
The aim of this study was to discuss the therapeutic mechanism of action of antimalarials, in particular hydroxychloroquine (HCQ), in patients with lupus erythematosus. It examines the results of recent studies indicating the need to revise the indications, dosage and duration of safe therapy, thus limiting the possibility of adverse effects. Historically, HCQ was recommended for patients with arthritis as a predominant symptom, whereas today, it is recommended for all lupus patients, even those with lupus nephritis and pregnant women; it has a favourable therapeutic profile, particularly regarding its effect on the activity of the disease, and the possibility of prolonging survival time and preventing organ damage and dysfunction. Antimalarials are basic, disease-modifying antirheumatic drugs, which not only relieve the symptoms of inflammation, but also affect the underlying processes; therefore, they should be administered chronically, and the expected effects may sometimes take a long time to become apparent. In the past, the recommended dose was 6.5 mg/kg ideal body weight, whereas today it is up to 5.0 mg/kg real body weight. A very important aspect of long-term therapy is the strict adherence to the medical prescription; hence, the introduction of a new formulation containing 400 mg of hydroxychloroquine sulphate per tablet is an interesting proposal.